The Effect of Carrying School Bag on Electromyographic Activity of Muscles and Biomechanical Parameters of Walking in Iranian Students: a Systematic Review Study - Parisa Sayyadi; Rahman Sheikhhoseini; Hashem Piri (Shiraz University of Medical Sciences, 2021)
Context: Carrying a backpack with an inappropriate weight and non-optimal postures play a pivotal role in developing musculoskeletal pain. Studies have shown that school bags affect muscle activity and biomechanical variables in children and adolescents. Accordingly, the present study aimed to systematically review the effect of school bags on electromyographic activity of muscles and kinematic and kinetic parameters during walking in Iranian students. Methods: Relevant articles were searched through Scopus, PubMed, Web of Science, MagIran, and SID databases. Original articles in Persian and English published in peer-review journals were selected without time limitation. Eligible studies were divided based on various biomechanical factors that were examined. Results: A total of 1975 articles were found in the mentioned databases. Twelve studies were eligible based on the inclusion criteria in this study. In general, it seems as though weight, type, the height of placement of schoolbag, slope of the surface, and the manner of carrying the schoolbag had significant effects on the trunk, neck, ankle, and knee angles, length and frequency of steps, symmetry index, and vertical forces. Additionally, the weight and type of the bag had significant effects on the electromyographic activity of rectus abdominus, paraspinal, and lower limb muscles. Conclusions: Factors such as weight, the slope of the surface, method of carrying, and schoolbag height of placement could affect the kinetic and kinematic variables whereas the weight of the bag and the type of school bag could affect the electromyographic activity of the muscles in Iranian students.